Communication Process in the Corruption Prevention Coordination Network in Teluk Bintuni Regency - Mas Juli; Alwi Alwi; Badu Ahmad (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Corruption remains a critical governance challenge as it undermines public trust and weakens accountability at the regional level. In Teluk Bintuni Regency, corruption risks are particularly evident in budget planning, procurement, and regional revenue management, all of which involve complex inter-agency coordination. This study aims to analyze how communication functions within the inter-agency coordination network for corruption prevention in Teluk Bintuni Regency and to identify key obstacles and enabling factors shaping this process. Using a qualitative case study approach, data were collected through in-depth interviews with officials from the Regional Inspectorate (APIP), law enforcement agencies (APH), and local government institutions, complemented by limited participant observation and document analysis. Data were analyzed using thematic analysis and interpreted through Robert T. Craig’s constitutive communication framework, which conceptualizes communication as a multidimensional process. The findings show that communication serves as the central foundation of coordination, operating through both formal and informal channels to build shared understanding, trust, and collaborative commitment. However, coordination remains constrained by fragmented information systems, divergent interpretations of authority, sectoral egos, and unequal power relations between institutions. The analysis reveals that effective corruption prevention communication encompasses rhetorical, semiotic, phenomenological, cybernetic, sociopsychological, sociocultural, and critical dimensions. The study concludes that strengthening corruption prevention in Teluk Bintuni requires institutionalized, integrative communication mechanisms that align meanings, support continuous feedback, manage power dynamics, and foster sustainable inter-agency collaboration.